Composite microsphere wave-absorbing material and preparation method thereof
By combining carbonyl iron powder with silane coupling agent and graphite, composite microsphere absorbing materials are formed, which solves the problems of complex processes, easy to pollute the environment and poor performance of the existing composite absorbing materials, and achieves lightweight, broadband and excellent absorbing performance.
Patent Information
- Application Number
- CN202311163786.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-07
- Publication Date
- 2025-03-07
AI Technical Summary
The existing composite wave absorbing materials have complex processes, are prone to polluting the environment and have poor performance.
By combining the carbonyl iron powder with a silane coupling agent and graphite, a composite microsphere absorbing material is formed in which the carbonyl iron powder, the coupling agent layer and the graphite cladding layer are arranged in sequence from the inside to the outside. The material forms microspheres through hydrogen bond adsorption, and the graphite cladding is uniformly embedded through a ball milling process.
It realizes a composite absorbing material with lightweight, wide frequency and excellent wave absorption performance, and the preparation method is simple and controllable, low-cost, large-scale production, environmentally friendly and pollution-free.
Smart Images

Figure CN119584517A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of wave absorbing materials, and in particular to a composite microsphere wave absorbing material and a preparation method thereof. Background Art
[0002] With the rapid development of information technology, electromagnetic interference has caused increasingly serious electromagnetic pollution. Although traditional absorbing materials such as metal magnets, ferrites and their composites have successfully achieved good electromagnetic wave absorption in some cases, they usually have a large load, high density and narrow absorption bandwidth, which makes it difficult to meet the "thin, light, wide and strong" characteristics required by new absorbing materials. One of the effective ways to solve this problem is to combine conventional magnetic materials with lightweight dielectric materials and utilize the synergistic effect between magnetic and dielectric components to improve microwave absorption performance. Carbon-based materials are usually the most attractive candidate materials because they have various excellent properties, including high dielectric constant, high corrosion resistance, low density and general processing performance.
[0003] Various carbon materials such as carbon fiber, carbon nanotubes, carbon black, graphene and porous carbon have become candidates for ideal electromagnetic absorbers in recent years due to their great advantages such as adjustable dielectric properties, low density and excellent chemical stability. However, most of these carbon materials have complex preparation methods, high costs and may even pollute the environment. As a traditional carbon material, flake graphite is a typical dielectric material. Flake graphite has a high dielectric constant, low density and low cost, simple preparation method and high temperature resistance, making it a preferred material for composite with magnetic materials.
[0004] The current methods for compounding carbon materials with magnetic materials, such as in-situ synthesis methods such as hydrothermal method and liquid phase method, have complex preparation processes and low yields, making it difficult to form large-scale production. Summary of the invention
[0005] The main purpose of the present invention is to provide a composite microsphere absorbing material and a preparation method thereof, so as to solve the problems of complex process, easy environmental pollution and poor performance of the composite absorbing material in the prior art.
[0006] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a composite microsphere absorbing material is provided, which comprises: carbonyl iron powder, a coupling agent layer and a graphite coating layer arranged in sequence from the inside to the outside; the coupling agent layer is adsorbed on the surface of the carbonyl iron powder through hydrogen bonds to form microspheres, and the microspheres are embedded in the graphite coating layer.
[0007] Further, the carbonyl iron powder is spherical or ellipsoidal, preferably the average particle size of the carbonyl iron powder is 2-3 μm, and preferably the purity of the carbonyl iron powder is ≥99%;
[0008] Preferably, the coupling agent layer is formed of a silane coupling agent;
[0009] Preferably, the silane coupling agent is any one or more of KH570, KH560 and KH792, and the thickness of the coupling agent layer is preferably 10-100 nm;
[0010] Preferably, the graphite coating layer has a thickness of 0.5-5 μm. Preferably, the graphite coating layer is formed of flake graphite.
[0011] According to another aspect of the present application, a method for preparing a composite microsphere absorbing material is provided, the method comprising: step S1, mixing carbonyl iron powder with a modified composition to obtain a dispersion, wherein the modified composition comprises a silane coupling agent, a solvent, and an alkaline solution; step S2, filtering the dispersion after standing for a period of time, and subjecting the solid component obtained after filtration to a first drying to obtain a modified carbonyl iron powder; step S3, adding the modified carbonyl iron powder and graphite to a ball milling device, ball milling, washing the obtained ball milling product, and subjecting the obtained ball milling product to a second drying to obtain the composite microsphere absorbing material.
[0012] Furthermore, the silane coupling agent is any one or more of KH570, KH560 and KH792, and the mass ratio of the silane coupling agent to the carbonyl iron powder in the modified composition is preferably 0.5-0.6:1.
[0013] Furthermore, the alkaline solution is selected from any one or more of aqueous ammonia, sodium hydroxide solution and potassium hydroxide solution; preferably the alkaline solution is aqueous ammonia.
[0014] Preferably, the amount of ammonia added is 1wt%-2wt% of the silane coupling agent;
[0015] Preferably, the modified composition further comprises water, and the amount of water added is preferably 20wt%-30wt% of the amount of the silane coupling agent added;
[0016] Preferably, the solvent is selected from any one or more of isopropanol, methanol, ethanol and propanol. Preferably, the mass ratio of the solvent to the carbonyl iron powder is 30 to 60:1.
[0017] Furthermore, the carbonyl iron powder is spherical or ellipsoidal, and preferably has an average particle size of 2-3 μm. Preferably, the iron content of the carbonyl iron powder is ≥99%.
[0018] Furthermore, the graphite is flake graphite, and preferably the mass ratio of graphite to modified carbonyl iron powder is 1:1.8-2.2.
[0019] Furthermore, step S1 comprises ultrasonically dispersing the carbonyl iron powder and the modified composition under stirring, and preferably the ultrasonic dispersing time is 8 to 30 minutes.
[0020] Furthermore, the standing time in step S2 is 4-8 hours; and the first drying is vacuum drying.
[0021] Furthermore, in step S3, a dispersing solvent is added to the ball mill, and preferably the dispersing solvent is selected from any one or more of ethanol, ethylene glycol, and propylene glycol;
[0022] Preferably, the ball milling medium is selected from zirconium oxide beads, and the diameter of the ball milling medium is preferably 1-5 mm;
[0023] Preferably, the ball-to-material ratio of ball milling is 10 to 15:1;
[0024] Preferably, the rotation speed of the ball mill is 400-800 r / min;
[0025] Preferably, the ball milling time is 40-60h, more preferably 48-52h;
[0026] Preferably, washing comprises washing with distilled water one or more times, and then washing with ethanol one or more times;
[0027] Preferably, the second drying temperature is 70-90°C and the time is 12-24 hours.
[0028] By applying the technical solution of the present invention, the composite microsphere absorbing material is coated with carbonyl iron powder on the basis of the bridge connection of the coupling agent layer, and the microwave absorption performance is improved by utilizing the synergistic effect between the magnetic and dielectric components. It is a composite absorbing material with light weight, broadband and excellent absorbing performance. The preparation method is simple and controllable, low-cost, mass-producible, environmentally friendly and pollution-free. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0030] Figure 1 A schematic diagram of the microstructure of a composite microsphere absorbing material according to an embodiment of the present invention is shown.
[0031] The above-mentioned drawings include the following reference numerals: 100, carbonyl iron powder; 200, coupling agent layer bridge; 300, graphite coating layer. DETAILED DESCRIPTION
[0032] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0033] As analyzed in the background technology of this application, traditional absorbing materials have high loading capacity, high density and narrow absorbing bandwidth, while existing composite absorbing materials have problems such as complex process, easy environmental pollution and poor performance. In order to solve these problems, this application provides a composite microsphere absorbing material and a preparation method thereof.
[0034] According to a typical embodiment of the present application, a composite microsphere absorbing material is provided, which includes: carbonyl iron powder, a coupling agent layer and a graphite coating layer arranged in sequence from the inside to the outside; wherein the coupling agent layer is adsorbed on the surface of the carbonyl iron powder through hydrogen bonds to form microspheres, and the microspheres are embedded in the graphite coating layer.
[0035] The composite microsphere absorbing material of the present application is a composite absorbing material with light dielectric material graphite coated with carbonyl iron powder on the basis of bridge connection of coupling agent layer, and the synergistic effect between magnetic and dielectric components is used to improve microwave absorption performance. It is a composite absorbing material with light weight, broadband and excellent absorbing performance. In addition, its preparation method is simple and controllable, low-cost, mass-producible, environmentally friendly and pollution-free.
[0036] The carbonyl iron powder can be selected from the prior art without any special requirements. In some embodiments of the present application, the carbonyl iron powder is spherical or ellipsoidal, which is close to a sphere, and is easier to evenly attach the coupling agent and combine with graphite. Preferably, the average particle size of the carbonyl iron powder is 2-3 μm, which helps to enhance the synergistic effect with graphite and improve the comprehensive performance of the composite absorbing material. Preferably, the purity of the carbonyl iron powder is ≥99%.
[0037] The coupling agent layer can be formed by a silane coupling agent, which can be selected from the prior art. In some preferred embodiments of the present application, the silane coupling agent is any one or more of KH570, KH560 and KH792, which can further reduce the surface energy of the carbonyl iron powder, make it firmly composite with graphite, and improve the performance of the composite material. Preferably, the thickness of the coupling agent layer is 10-100nm, which can better take into account the microwave absorption performance of the composite material and the morphology control of the carbonyl iron powder and graphite.
[0038] In some preferred embodiments of the present application, the thickness of the graphite coating layer is 0.5-5 μm. Preferably, the graphite coating layer is formed of flake graphite.
[0039] In some embodiments of the present application, the microstructure of the composite microsphere absorbing material is as follows: Figure 1As shown, it includes carbonyl iron powder 100 located in the innermost layer, coupling agent layer bridge 200 coated on the surface of carbonyl iron powder, and graphite coating layer 300 located in the outermost layer. Through a simple mechanical ball milling process, with the help of the coupling agent layer bridge, graphite particles are assembled on the surface of spherical carbonyl iron to form a graphite-coated carbonyl iron composite microsphere with a core-shell structure. Due to the synergistic effect between the magnetic loss and the dielectric loss between the inner and outer layers of the core-shell structure, the composite microsphere exhibits excellent electromagnetic wave absorption performance. At the same time, the mass ratio of carbonyl iron powder and graphite can be controlled to adjust the absorption performance of the composite absorber.
[0040] According to another typical embodiment of the present application, a method for preparing a composite microsphere absorbing material is provided, and the preparation method comprises: step S1, mixing carbonyl iron powder with a modified composition to obtain a dispersion, wherein the modified composition comprises a silane coupling agent, a solvent, and an alkaline solution; step S2, filtering the dispersion after standing for a period of time, and subjecting the solid component obtained after filtration to a first drying to obtain a modified carbonyl iron powder; step S3, adding the modified carbonyl iron powder and graphite to a ball milling device, ball milling, washing the obtained ball milling product, and subjecting the composite microsphere absorbing material to a second drying.
[0041] The present invention uses a silane coupling agent to modify the surface of traditional carbonyl iron powder, reducing its surface energy. On the one hand, it can effectively prevent the carbonyl iron powder from agglomerating, and on the other hand, it is conducive to the uniform coating of graphite on its surface, thereby realizing the morphology control of the composite material, and greatly improving the wave absorption performance of the composite material. During the modification, the concentration of the alkaline solution is added to control the hydrolysis rate of the silane coupling agent, so that the hydrolysis product formed by the coupling agent is adsorbed on the surface of the carbonyl iron in a large area, which is conducive to the adhesion of graphite and forms a firm core-shell structure. Through a simple mechanical ball milling process, the graphite particles are assembled on the surface of the spherical carbonyl iron. Due to the synergistic effect between the magnetic loss and the dielectric loss between the inner and outer layers of the core-shell structure, the composite microspheres show excellent electromagnetic wave absorption performance, and while meeting the larger absorption intensity, they also have the characteristics of light weight, broadband, good stability, etc. The preparation method is simple, controllable, low-cost, large-scale production, environmentally friendly, pollution-free, and can meet the protection needs of large-scale electromagnetic equipment.
[0042] The above-mentioned silane coupling agent can be selected from the prior art. In some preferred embodiments of the present application, the silane coupling agent is any one or more of KH570, KH560 and KH792, which can further reduce the surface energy of the carbonyl iron powder, make it firmly composite with graphite, and improve the performance of the composite material. Preferably, the mass ratio of the silane coupling agent to the carbonyl iron powder in the modified composition is 0.5-0.6:1, which has a good modification effect on the carbonyl iron powder and is more conducive to the performance of the composite material.
[0043] The addition of the above-mentioned alkaline solution can cause the silane coupling agent to partially hydrolyze, and the hydrolysis product is adsorbed on the surface of the carbonyl iron powder and attached to the surface of the graphite particles to form a core-shell structure. In some embodiments of the present application, the above-mentioned alkaline solution is selected from any one or more of ammonia water, sodium hydroxide solution and potassium hydroxide solution. In particular, when the alkaline solution is ammonia water, it is not only convenient for acid-base adjustment, but also does not introduce other ions after heat treatment, which is more beneficial to improving the comprehensive performance of the composite microspheres. Preferably, the pH value of the modified composition is 10-12, and the hydrolysis rate of the silane coupling agent is adjusted by controlling the acidity and alkalinity of the modified composition. The appropriate hydrolysis rate is conducive to the large-area adsorption of the hydrolysis product formed by the coupling agent on the surface of the carbonyl iron.
[0044] In some embodiments of the present application, the pH value of the modified composition is higher than the above pH value range after adding only the alkaline solution, therefore, the modified composition also includes water. In some embodiments of the present application, in order to facilitate the determination of the amount of alkaline solution and water in the composition, the concentration of ammonia water in the modified composition is 26wt%, and the amount added is 1wt%-2wt% of the silane coupling agent, and preferably the amount of water added is 20wt%-30wt% of the amount of the silane coupling agent added.
[0045] In some typical embodiments of the present application, the carbonyl iron powder is first mixed with the solvent and the silane coupling agent in the modified composition, and then ammonia water is added, and then deionized water is added to a pH value of 10-12 to better control the hydrolysis rate of the silane coupling agent, thereby better adsorbing it on the surface of the carbonyl iron.
[0046] The solvent in the modified composition can be selected from the prior art. In some embodiments of the present application, the solvent is selected from any one or more of isopropanol, methanol, ethanol and propanol, which is more conducive to the hydrolysis of the silane coupling agent at an appropriate rate. Preferably, the mass ratio of the solvent to the carbonyl iron powder is 30 to 60:1, which is conducive to promoting the adsorption of the silane coupling agent on the surface of the carbonyl iron powder.
[0047] The above-mentioned carbonyl iron powder can be selected from the prior art. For example, the carbonyl iron powder used is spherical or ellipsoidal. In some preferred embodiments of the present application, the average particle size of the carbonyl iron powder is 2-3 μm, which helps to enhance the synergistic effect with graphite and improve the comprehensive performance of the composite absorbing material. Preferably, the purity of the carbonyl iron powder is ≥99%.
[0048] The above-mentioned graphite can be selected from the prior art, and the graphite is preferably flake graphite, which is convenient for coating on the surface of carbonyl iron powder microspheres modified by coupling agents. Compared with graphite oxide and reduced graphene oxide, graphite does not have a large number of oxygen-containing functional groups and a large interlayer spacing. Without introducing other chemical reagents, it is difficult to composite graphite with micron-level carbonyl iron powder. The present invention uses a silane coupling agent to modify the surface of traditional carbonyl iron powder to reduce its surface energy. On the one hand, it can effectively prevent the agglomeration of carbonyl iron powder, and on the other hand, it is conducive to the uniform coating of graphite on its surface, thereby realizing the morphology control of the composite material and greatly improving the wave absorption performance of the composite material. The wave absorption performance of the composite absorber can be regulated by controlling the mass ratio of carbonyl iron powder and graphite. Preferably, the mass ratio of graphite to the above-mentioned modified carbonyl iron powder is 1:1.8-2.2, which is more conducive to realizing the synergistic effect between the magnetic loss and dielectric loss between the inner and outer layers of the core-shell structure, so that the composite microspheres exhibit excellent electromagnetic wave absorption performance.
[0049] In some typical embodiments of the present application, the above step S1 includes ultrasonically dispersing the carbonyl iron powder and the modified composition under stirring, which is conducive to the uniform dispersion and adsorption of the modified composition and the carbonyl iron powder. The ultrasonic dispersion time is preferably 8 to 30 minutes, which has a better effect. In some embodiments of the present application, the standing time in step S2 is 4-8 hours, so that the silane coupling agent is fully hydrolyzed and adsorbed on the surface of the carbonyl iron powder; in some embodiments of the present application, the above first drying is vacuum drying, which is conducive to improving the drying efficiency.
[0050] The specific processing method of the above-mentioned ball milling can be determined according to the prior art, and wet milling is preferably used, that is, in step S3, a dispersing solvent is also added to the ball milling device, and the dispersing solvent is preferably selected from any one or more of ethanol, ethylene glycol, and propylene glycol; through a simple mechanical ball milling process, the graphite particles are assembled to the surface of the spherical carbonyl iron to form a core-shell structure of graphite-coated carbonyl iron composite microspheres. Preferably, the ball milling medium is selected from zirconium oxide beads, which has a better grinding effect, and the product obtained by grinding is more uniform, has fewer impurities, and has better comprehensive performance. Preferably, the diameter of the ball milling medium is 1-5mm, which can further improve the grinding effect and promote the synergistic effect of the graphite-coated carbonyl iron composite microspheres. Preferably, the ball-to-material ratio of the ball milling is 10 to 15:1, and the grinding efficiency is relatively high. Preferably, the rotation speed of the ball milling device is 400-800r / min; in some embodiments of the present application, the ball milling time is 40-60h, more preferably 48-52h. By controlling the ball milling time, the impedance matching characteristics of the composite absorber can be effectively improved. This is mainly because the ball milling time can effectively adjust the morphology and conductivity of the graphite-coated carbonyl iron composite microspheres. Within the appropriate ball milling time, the good dielectric loss of the graphite material can be maintained, and at the same time, the layered structure of the graphite is destroyed during the ball milling process, resulting in lamella separation and a reduction in particle size, thereby greatly reducing its conductivity, significantly improving the impedance matching performance of the composite absorbent material, and greatly enhancing the composite absorbent material's absorption of electromagnetic waves.
[0051] After the ball milling is completed, the ball milling mixture is taken out for washing. In some embodiments of the present application, the washing includes washing with ethanol one or more times, and then washing with water one or more times to separate the fine powder attached to the surface of the microspheres. In some embodiments of the present application, the temperature of the second drying is 70-90°C, the time is 12-24h, the drying efficiency is high, and the obtained composite microsphere absorbing material has a strong structure and excellent performance.
[0052] The beneficial effects that can be achieved by the present application will be further illustrated below in combination with embodiments and comparative examples.
[0053] Example 1
[0054] The specific preparation method of a composite microsphere absorbing material with a graphite-coated carbonyl iron core-shell structure is as follows:
[0055] 1) 65 g of carbonyl iron powder (provided by Shaanxi Xuliheng New Materials Co., Ltd., model MCIP-R-2, purity greater than 99%, average particle size 2-3 μm), 500 ml of isopropanol, and 32.5 g of KH570 silane coupling agent were added to a 1L three-necked flask in sequence, and then 1% of ammonia water (concentration 26%) and 20% of deionized water were added to the three-necked flask, and the above solution was ultrasonically dispersed under strong magnetic stirring for 20 minutes to obtain a suspension.
[0056] 2) The suspension is allowed to stand at room temperature for 24 hours and filtered, and the filtrate is vacuum dried at 80° C. to obtain the modified carbonyl iron powder.
[0057] 3) Add 20g of flake graphite (provided by Zhengzhou Hengchang Metal Materials Factory, with an average lateral size of 10μm), 36g of the above-mentioned modified carbonyl iron powder, and 50mL of ethanol into a 1L ceramic ball mill, and then add zirconium oxide beads into the ball mill. The ratio of zirconium oxide beads is 1 part of 1mm zirconium beads, 2 parts of 3mm zirconium beads, and 1 part of 5mm zirconium beads. Keep the ball-to-material ratio in the jar at 10:1. Finally, seal the ball mill and install it on a planetary ball mill. Rapid ball milling is carried out at a speed of 800 rpm, and the ball milling time is controlled to be 48h.
[0058] 4) After the ball milling is completed, the ball milling mixture is taken out, washed three times with alcohol and deionized water respectively, filtered and dried at 80° C. for 12 h to obtain a composite microsphere absorbing material with a graphite-coated carbonyl iron core-shell structure.
[0059] Example 2
[0060] The specific preparation method of a composite microsphere absorbing material with a graphite-coated carbonyl iron core-shell structure is as follows:
[0061] 1) 65 g of carbonyl iron powder (same as in Example 1), 500 ml of isopropanol, and 35.5 g of KH570 silane coupling agent were added to a 1 L three-necked flask in sequence, and then 1.5% of ammonia water (concentration of 26%) and 25% of deionized water were added to the three-necked flask, and the above solution was ultrasonically dispersed for 20 min under strong magnetic stirring to obtain a suspension.
[0062] 2) The suspension is allowed to stand at room temperature for 24 hours and filtered, and the filtrate is vacuum dried at 80° C. to obtain the modified carbonyl iron powder.
[0063] 3) 20 g of graphite (same as in Example 1), 40 g of the modified carbonyl iron powder and 50 mL of ethanol were added to a 1 L ceramic ball mill, and then zirconium oxide beads were added to the ball mill. The ratio of zirconium oxide beads was 1 part of 1 mm zirconium beads, 2 parts of 3 mm zirconium beads and 1 part of 5 mm zirconium beads. The ball-to-material ratio in the jar was kept at 10:1. Finally, the ball mill was sealed and installed on a planetary ball mill, and rapid ball milling was performed at a speed of 800 rpm. The ball milling time was controlled to be 52 h.
[0064] 4) After the ball milling is completed, the ball milling mixture is taken out, washed three times with alcohol and deionized water respectively, filtered and dried at 80° C. for 12 h to obtain a composite microsphere absorbing material with a graphite-coated carbonyl iron core-shell structure.
[0065] Example 3
[0066] The specific preparation method of a composite microsphere absorbing material with a graphite-coated carbonyl iron core-shell structure is as follows:
[0067] 1) 65 g of carbonyl iron powder (same as in Example 1), 500 ml of isopropanol, and 39 g of KH570 silane coupling agent were added to a 1 L three-necked flask in sequence, and then 1.5% of ammonia water (concentration of 26%) and 25% of deionized water were added to the three-necked flask, and the above solution was ultrasonically dispersed for 20 min under strong magnetic stirring to obtain a suspension.
[0068] 2) The suspension is allowed to stand at room temperature for 24 hours and filtered, and the filtrate is vacuum dried at 80° C. to obtain the modified carbonyl iron powder.
[0069] 3) 20 g of graphite (same as in Example 1), 44 g of the modified carbonyl iron powder and 50 mL of ethanol were added to a 1 L ceramic ball mill, and then zirconium oxide beads were added to the ball mill. The ratio of zirconium oxide beads was 1 part of 1 mm zirconium beads, 2 parts of 3 mm zirconium beads and 1 part of 5 mm zirconium beads. The ball-to-material ratio in the jar was kept at 10:1. Finally, the ball mill was sealed and installed on a planetary ball mill, and rapid ball milling was performed at a speed of 800 rpm. The ball milling time was controlled to be 56 h.
[0070] 4) After the ball milling is completed, the ball milling mixture is taken out, washed three times with alcohol and deionized water respectively, filtered and dried at 80° C. for 12 h to obtain a composite microsphere absorbing material with a graphite-coated carbonyl iron core-shell structure.
[0071] Example 4
[0072] The specific preparation method of a composite microsphere absorbing material with a graphite-coated carbonyl iron core-shell structure is as follows:
[0073] 1) 65 g of carbonyl iron powder (provided by Shaanxi Xuliheng New Materials Co., Ltd., model MCIP-R-2, purity greater than 99%, particle size 2-3 μm), 500 ml of isopropanol, and 32.5 g of KH570 silane coupling agent were added to a 1 L three-necked flask in sequence, and then 1% of the mass of the silane coupling agent (concentration of 26%) and 20% of deionized water were added to the three-necked flask, and the above solution was ultrasonically dispersed under strong magnetic stirring for 20 min to obtain a suspension.
[0074] 2) The suspension is allowed to stand at room temperature for 24 hours and filtered, and the filtrate is vacuum dried at 80° C. to obtain the modified carbonyl iron powder.
[0075] 3) Add 20g of graphite (provided by Zhengzhou Hengchang Metal Materials Factory, with an average lateral size of 10μm), 36g of the above-mentioned modified carbonyl iron powder, and 50mL of ethanol into a 1L ceramic ball mill, and then add zirconium oxide beads into the ball mill. The ratio of zirconium oxide beads is 1 part of 1mm zirconium beads, 2 parts of 3mm zirconium beads, and 1 part of 5mm zirconium beads. Keep the ball-to-material ratio in the jar at 10:1. Finally, seal the ball mill and install it on a planetary ball mill. Rapid ball milling is carried out at a speed of 800 rpm, and the ball milling time is controlled to be 60h.
[0076] 4) After the ball milling is completed, the ball milling mixture is taken out, washed three times with alcohol and deionized water respectively, filtered and dried at 80° C. for 12 h to obtain a composite microsphere absorbing material with a graphite-coated carbonyl iron core-shell structure.
[0077] Example 5
[0078] The specific preparation method of a composite microsphere absorbing material with a graphite-coated carbonyl iron core-shell structure is as follows:
[0079] 1) 65 g of carbonyl iron powder (provided by Shaanxi Xuliheng New Materials Co., Ltd., model MCIP-R-2, purity greater than 99%, particle size 2-3 μm), 500 ml of isopropanol, and 39 g of KH570 silane coupling agent were added to a 1L three-necked flask in sequence, and then 2% of ammonia water (concentration 26%) and 30% of deionized water were added to the three-necked flask, and the above solution was ultrasonically dispersed under strong magnetic stirring for 20 min to obtain a suspension.
[0080] 2) The suspension is allowed to stand at room temperature for 24 hours and filtered, and the filtrate is vacuum dried at 80° C. to obtain the modified carbonyl iron powder.
[0081] 3) Add 20g of graphite (provided by Zhengzhou Hengchang Metal Materials Factory, with an average lateral size of 10μm), 44g of the modified carbonyl iron powder, and 50mL of ethanol into a 1L ceramic ball mill, and then add zirconium oxide beads into the ball mill. The ratio of zirconium oxide beads is 1 part of 1mm zirconium beads, 2 parts of 3mm zirconium beads, and 1 part of 5mm zirconium beads. Keep the ball-to-material ratio in the jar at 10:1. Finally, seal the ball mill and install it on a planetary ball mill. Rapid ball milling is carried out at a speed of 800 rpm, and the ball milling time is controlled to be 48h.
[0082] 4) After the ball milling is completed, the ball milling mixture is taken out, washed three times with alcohol and deionized water respectively, filtered and dried at 80° C. for 12 h to obtain a composite microsphere absorbing material with a graphite-coated carbonyl iron core-shell structure.
[0083] Example 6
[0084] The specific preparation method of a composite microsphere absorbing material with a graphite-coated carbonyl iron core-shell structure is as follows:
[0085] 1) 65 g of carbonyl iron powder (provided by Shaanxi Xuliheng New Materials Co., Ltd., model MCIP-R-2, purity greater than 99%, particle size 2-3 μm), 500 ml of isopropanol, and 35.5 g of KH570 silane coupling agent were added to a 1L three-necked flask in sequence, and then 1% of the mass of the silane coupling agent (concentration of 26%) and 30% of deionized water were added to the three-necked flask, and the above solution was ultrasonically dispersed under strong magnetic stirring for 20 minutes to obtain a suspension.
[0086] 2) The suspension is allowed to stand at room temperature for 24 hours and filtered, and the filtrate is vacuum dried at 80° C. to obtain the modified carbonyl iron powder.
[0087] 3) 20 g of graphite (provided by Zhengzhou Hengchang Metal Materials Factory, with an average lateral size of 10 μm), 40 g of the modified carbonyl iron powder, and 50 mL of ethanol were added to a 1 L ceramic ball mill, and then zirconium oxide beads were added to the ball mill. The ratio of zirconium oxide beads was 1 part of 1 mm zirconium beads, 2 parts of 3 mm zirconium beads, and 1 part of 5 mm zirconium beads. The ball-to-material ratio in the jar was maintained at 10:1. Finally, the ball mill was sealed and installed on a planetary ball mill, and rapid ball milling was performed at a speed of 800 rpm. The ball milling time was controlled to be 52 h.
[0088] 4) After the ball milling is completed, the ball milling mixture is taken out, washed three times with alcohol and deionized water respectively, filtered and dried at 80° C. for 12 h to obtain a composite microsphere absorbing material with a graphite-coated carbonyl iron core-shell structure.
[0089] Example 7
[0090] The specific preparation method of a composite microsphere absorbing material with a graphite-coated carbonyl iron core-shell structure is as follows:
[0091] 1) 65 g of carbonyl iron powder (provided by Shaanxi Xuliheng New Materials Co., Ltd., model MCIP-R-2, purity greater than 99%, particle size 2-3 μm), 500 ml of isopropanol, and 32.5 g of KH570 silane coupling agent were added to a 1 L three-necked flask in sequence, and then 2% of ammonia water (concentration 26%) and 20% of deionized water were added to the three-necked flask, and the above solution was ultrasonically dispersed under strong magnetic stirring for 20 min to obtain a suspension.
[0092] 2) The suspension is allowed to stand at room temperature for 24 hours and filtered, and the filtrate is vacuum dried at 80° C. to obtain the modified carbonyl iron powder.
[0093] 3) 20 g of graphite (provided by Zhengzhou Hengchang Metal Materials Factory, with an average lateral size of 10 μm), 40 g of the modified carbonyl iron powder, and 50 mL of ethanol were added to a 1 L ceramic ball mill, and then zirconium oxide beads were added to the ball mill. The ratio of zirconium oxide beads was 1 part of 1 mm zirconium beads, 2 parts of 3 mm zirconium beads, and 1 part of 5 mm zirconium beads. The ball-to-material ratio in the jar was maintained at 10:1. Finally, the ball mill was sealed and installed on a planetary ball mill, and rapid ball milling was performed at a speed of 800 rpm. The ball milling time was controlled to be 52 h.
[0094] 4) After the ball milling is completed, the ball milling mixture is taken out, washed three times with alcohol and deionized water respectively, filtered and dried at 80° C. for 12 h to obtain a composite microsphere absorbing material with a graphite-coated carbonyl iron core-shell structure.
[0095] Example 8
[0096] The only difference from Example 1 is that the ball milling time is 52 h.
[0097] Example 9
[0098] The only difference from Example 1 is that the ball milling time is 40 h.
[0099] Example 10
[0100] The only difference from Example 1 is that only ammonia water is added without adding deionized water, the concentration of ammonia water is 1.2%, and the amount added is 21% of the mass of the silane coupling agent.
[0101] Embodiment 11
[0102] The only difference from Example 1 is that the amount of ammonia water added is 2% of the mass of the silane coupling agent.
[0103] Example 12
[0104] The only difference from Example 1 is that the amount of ammonia water added is 0.5% of the mass of the silane coupling agent.
[0105] Embodiment 13
[0106] The only difference from Example 1 is that the amount of water added in step 1) is 30% of the mass of the silane coupling agent.
[0107] Embodiment 14
[0108] The only difference from Example 1 is that the added amount of the modified carbonyl iron powder is 50 g.
[0109] Embodiment 15
[0110] The only difference from Example 1 is that the carbonyl iron powder of Example 1 is replaced by MCIP-R-2 model carbonyl iron powder (average particle size 2.5-3 μm) provided by Shaanxi Xinghua Group Co., Ltd.
[0111] Example 16
[0112] The only difference from Example 1 is that the flake graphite of Example 1 is replaced by non-flake carbon graphite of the same quality (provided by Beijing Gaoke New Material Technology Co., Ltd., with an average particle size of 5 μm and an elliptical shape).
[0113] Embodiment 17
[0114] The only difference from Example 1 is that the flake graphite in Example 1 is replaced by graphite oxide of the same mass (provided by Nanjing Xianfeng Nanomaterial Technology Co., Ltd., with an average particle size of 0.5-5 μm).
[0115] Embodiment 18
[0116] The only difference from Example 1 is that KH560 silane coupling agent is used to replace KH570 silane coupling agent.
[0117] Comparative Example 1
[0118] 1) 40 g of unmodified carbonyl iron powder (same as in Example 1) and 50 mL of ethanol were added to a 1 L ceramic ball mill, and then zirconium oxide beads were added to the ball mill. The ratio of zirconium oxide beads was 1 part of 1 mm zirconium beads, 2 parts of 3 mm zirconium beads, and 1 part of 5 mm zirconium beads. The ball-to-material ratio in the jar was maintained at 10:1. Finally, the ball mill was sealed and installed on a planetary ball mill, and rapid ball milling was performed at a speed of 800 rpm. The ball milling time was controlled to be 52 h.
[0119] 2) After the ball milling is completed, the ball milling mixture is taken out, washed three times with alcohol and deionized water respectively, filtered and dried at 80° C. for 12 hours to obtain a carbonyl iron absorbing material.
[0120] Comparative Example 2
[0121] 1) 20 g of graphite oxide (provided by Nanjing Xianfeng Nanomaterial Technology Co., Ltd., with a particle size of 0.5-5 μm), 40 g of unmodified carbonyl iron powder, and 50 mL of ethanol were added to a 1 L ceramic ball mill, and then zirconium oxide beads with a diameter of 1-5 mm were placed into the ball mill, and the ball-to-material ratio in the mill was maintained at 10:1. Finally, the ball mill was sealed and installed on a planetary ball mill, and rapid ball milling was performed at a speed of 800 rpm, and the ball milling time was controlled to be 52 h.
[0122] 2) After the ball milling is completed, the ball milling mixture is taken out, washed three times with alcohol and deionized water respectively, filtered and dried at 80° C. for 12 h to obtain a graphite oxide-coated carbonyl iron absorbing material.
[0123] Comparative Example 3
[0124] 1) 20 g of reduced graphite oxide (provided by Nanjing Xianfeng Nanomaterial Technology Co., Ltd., with a particle size of 0.5-5 μm), 40 g of unmodified carbonyl iron powder, and 50 mL of ethanol were added to a 1 L ceramic ball mill, and then zirconium oxide beads with a diameter of 1-5 mm were placed into the ball mill, and the ball-to-material ratio in the mill was maintained at 10:1. Finally, the ball mill was sealed and installed on a planetary ball mill, and rapid ball milling was performed at a speed of 800 rpm, and the ball milling time was controlled to be 52 h.
[0125] 2) After the ball milling is completed, the ball milling mixture is taken out, washed three times with alcohol and deionized water respectively, filtered and dried at 80° C. for 12 h to obtain a reduced graphite oxide-coated carbonyl iron absorbing material.
[0126] The absorbing materials obtained in the above-mentioned embodiment and comparative example were tested for reflection loss and tap density, and the test results are shown in Table 1.
[0127] Among them, the reflection loss is calculated by the electromagnetic parameters of the material according to Formula 1 and Formula 2, and the electromagnetic parameters are obtained by testing the sample using the coaxial method through a network vector analyzer. The specific method is: first, the test sample is ground into powder and evenly mixed with molten paraffin in a ratio of 7:3, and then die-cast into a uniform ring of the required specifications (ring outer diameter 7.0mm, inner diameter 3.0mm, thickness 2.0mm) through a mold. Finally, the sample is placed in a coaxial cable, and the electromagnetic parameters in the frequency range of 1-18GHz are tested using a network vector analyzer, where the frequency band of the absorbing material with RL<-10dB represents the effective absorbing frequency band.
[0128] Among them, the tap density is obtained by measuring with a tap density meter. The specific method is: add a certain mass of powder absorbing material into a measuring cylinder, and fix the measuring cylinder on the vibration table of the tap density meter. After setting the vibration parameters, start vibration. After the vibration ends, read the powder volume and calculate the tap density value of the absorbing material.
[0129]
[0130] RL=2010g|(Z in -Z0) / (Z in +Z0)| (2)
[0131] Where: RL is the reflection loss of electromagnetic waves / dB;
[0132] c is the speed of light / 3.6*108 m / s;
[0133] Z0 is the free space wave impedance / Ω;
[0134] Z in Input wave impedance / Ω for the absorbing material;
[0135] μ r is the relative dielectric constant of the absorbing material;
[0136] ε r is the relative magnetic permeability of the absorbing material;
[0137] f is the frequency of the incident electromagnetic wave / Hz;
[0138] d is the thickness of the absorbing material / m;
[0139] h is the thickness of the absorbing material / m;
[0140] j is the imaginary unit.
[0141] Table 1
[0142]
[0143]
[0144] From the above description, it can be seen that the above-mentioned embodiments of the present invention achieve the following technical effects: by using a silane coupling agent to modify the surface of the traditional carbonyl iron powder, its surface energy is reduced. On the one hand, it can effectively prevent the carbonyl iron powder from agglomerating, and on the other hand, it is conducive to the uniform coating of graphite on its surface, thereby realizing the morphology control of the composite material, and greatly improving the wave absorption performance of the composite material. During the modification, the hydrolysis rate of the silane coupling agent is controlled by adjusting the pH value of the solution, so that the hydrolysis product formed by the coupling agent is adsorbed on the surface of the carbonyl iron over a large area, which is conducive to the adhesion of graphite and the formation of a firm core-shell structure. Through a simple mechanical ball milling process, the graphite particles are assembled on the surface of the spherical carbonyl iron. Due to the synergistic effect between the magnetic loss and the dielectric loss between the inner and outer layers of the core-shell structure, the composite microspheres exhibit excellent electromagnetic wave absorption performance, and while meeting the larger absorption intensity, they also have the characteristics of light weight, broadband, and good stability. The preparation method is simple, controllable, low-cost, and can be mass-produced. It is environmentally friendly and pollution-free, and can meet the protection needs of large-scale electromagnetic equipment.
[0145] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A composite microsphere absorbing material, characterized in that: include: Carbonyl iron powder, coupling agent layer and graphite coating layer are arranged in sequence from inside to outside; The coupling agent layer is adsorbed on the surface of the carbonyl iron powder through hydrogen bonds to form microspheres, and the microspheres are embedded in the graphite coating layer.
2. The composite microsphere absorbing material according to claim 1, characterized in that: The carbonyl iron powder is spherical or ellipsoidal, preferably the average particle size of the carbonyl iron powder is 2-3 μm, and preferably the purity of the carbonyl iron powder is ≥99%; Preferably, the coupling agent layer is formed by a silane coupling agent; Preferably, the silane coupling agent is any one or more of KH570, KH560 and KH792, and the thickness of the coupling agent layer is preferably 10-100 nm; Preferably, the graphite coating layer has a thickness of 0.5-5 μm. Preferably, the graphite coating layer is formed of flake graphite.
3. A method for preparing a composite microsphere absorbing material, characterized in that: include: Step S1, mixing carbonyl iron powder with a modified composition to obtain a dispersion, wherein the modified composition includes a silane coupling agent, a solvent, and an alkaline solution; Step S2, filtering the dispersion after standing for a period of time, and subjecting the solid component obtained after filtration to a first drying to obtain modified carbonyl iron powder; Step S3, adding the modified carbonyl iron powder and graphite into a ball milling device for ball milling, washing the obtained ball milling product, and performing a second drying to obtain the composite microsphere absorbing material.
4. The preparation method according to claim 3, characterized in that: The silane coupling agent is any one or more of KH570, KH560 and KH792. Preferably, the mass ratio of the silane coupling agent to the carbonyl iron powder in the modified composition is 0.5-0.6:
1.
5. The preparation method according to claim 3, characterized in that: The alkaline solution is selected from any one or more of ammonia water, sodium hydroxide solution and potassium hydroxide solution; preferably, the alkaline solution is ammonia water. Preferably, the amount of ammonia water added is 1wt%-2wt% of the silane coupling agent; Preferably, the modified composition further comprises water, and the amount of water added is preferably 20wt%-30wt% of the amount of the silane coupling agent added; Preferably, the solvent is selected from any one or more of isopropanol, methanol, ethanol and propanol. Preferably, the mass ratio of the solvent to the carbonyl iron powder is 30 to 60:
1.
6. The preparation method according to claim 3, characterized in that: The carbonyl iron powder is spherical or ellipsoidal, and preferably, the average particle size of the carbonyl iron powder is 2-3 μm. Preferably, the iron content of the carbonyl iron powder is ≥99%.
7. The preparation method according to claim 3, characterized in that: The graphite is flake graphite, and preferably the mass ratio of the graphite to the modified carbonyl iron powder is 1:1.8-2.
2.
8. The preparation method according to any one of claims 3 to 7, characterized in that: The step S1 comprises ultrasonically dispersing the carbonyl iron powder and the modified composition under stirring, and preferably the ultrasonic dispersing time is 8 to 30 minutes.
9. The preparation method according to any one of claims 3 to 7, characterized in that: The standing time in step S2 is 4-8 hours; the first drying is vacuum drying.
10. The preparation method according to any one of claims 3 to 7, characterized in that: In the step S3, a dispersing solvent is further added to the ball mill, and the dispersing solvent is preferably selected from any one or more of ethanol, ethylene glycol, and propylene glycol; Preferably, the ball milling medium is selected from zirconium oxide beads, and preferably the diameter of the ball milling medium is 1-5 mm; Preferably, the ball-to-material ratio of the ball mill is 10 to 15:1; Preferably, the rotation speed of the ball mill is 400-800r / min; Preferably, the ball milling time is 40-60h, more preferably 48-52h; Preferably, the washing comprises washing with distilled water one or more times, and then washing with ethanol one or more times; Preferably, the temperature of the second drying is 70-90° C. and the time is 12-24 hours.
Citation Information
Cited By
Graphene oxide coated carbonyl iron powder composite material and preparation method thereof
CN120421506A